The Effect of Online Learning System Through Blended Learning Model toward Higher Students' Academic Achievement - Nurdiyanti, Nurdiyanti; Rajab, Abd.; Sudarsono, Sudarsono; Sirajuddin, Sirajuddin (Journal of Biology Education, 2019)
Era industry 4.0, especially in the field of education, emphasizes the use of digital technology and the internet which develops rapidly in the learning process. Online learning is one form of implementation of learning in industry 4.0 era. The purpose of this study is to determine the effect of the implementation of the learning system on the higher students’ academic achievement. This research is experimental research, with a pretest-posttest control group design. The purpose of this design is to reveal whether online learning systems can affect students' academic achievement or not that's measured through the learning outcomes of biology education students at the concept of structure and transport of cell membranes in the University of Muhammadiyah Makassar. Based on analyzed data, it shows the difference in the increase of students' learning outcomes taught by the online learning system and without using an online learning system. Based on the findings of this study, students who are taught by online learning system get a higher score of learning outcomes. It can be said that there is an effect of the online learning system toward students’ academic achievement.